Pengaruh Citra Merek Dan Potongan Harga Terhadap Minat Beli (Studi Kasus Pada Distro Three Second di Kota Cilegon) - Muhamad Suhaemi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2020)
Competition in the business world is a challenge for the three second, three second always displays clothing models that are characteristic of young people, three second is a distribution that is well known among the public, especially in the city of Cilegon. (1) Is there an effect of brand image on buying interest in three second distribution in Cilegon City (2) Is there an effect of price discount on buying interest in three second distribution in Cilegon City (3) Is there an effect of brand image and price discount on buying interest . This study aims to examine the effect of brand image and price discounts on buying interest in a three second distribution in the city of Cilegon. The data collection method used was a questionnaire, with a population of 122 people, the number of samples used in this study were 94 people. Then the data were analyzed with SPSS version 2.0. (1) the results of the calculation show a significance value of 0.00 <0.05 or Tcount 4.034> 1.661 T table can be stated that brand image has an effect on buying interest. (2) the calculation shows a significance value of 0.00 <0.05 or Tcount 4.297> 1.661 T table, thus that the price discount is quite influential on buying interest. (3) The results of statistical calculations show 14,906> 3.10 F table with a significant level of 0.000 <0.05, so Ho is rejected. So with this it can be concluded that the variable Brand Image (X1) and Price Discounts (X2) simultaneously have a significant effect on Purchase Interest (Y).